EVALUATION OF THE PHYSICAL EDUCATION SPORTS AND HEALTH CURRICULUM FOR JUNIOR HIGH SCHOOL - Toteles, A Risky Heris; Pratama, Raditya (Four Son Scholarship, 2023)
This study used a sample of participants taken from a population of 31 participants. The sample is done not by random sampling but in a pandemic situation the sample is directly designated as needed. The sample required as many as 31 participants are participants who work in the Junior Secondary Education Unit. Based on the results of qualitative data in the form of conclusions and suggestions that have been obtained, it can be concluded that the curricular objectives of physical education and sports, student learning experience, curriculum structuring, curriculum practicality and the results of curriculum implementation in general do not meet the feasibility of curriculum evaluation of physical education subjects sports and health although with notes such as curriculum must keep up with the Times and in accordance with needs. In addition, the curriculum should be able to help the teacher to plan a lesson. A very constructive suggestion in the form of a curriculum is expected to be used and easy to use in the subjects of Physical Education Sports and health . There are further developments and improvements to refine the curriculum of physical education, sports and health subjects. Aspects of physical education and sports curricular objectives, student learning experience, curriculum structuring, curriculum practicality and the results of curriculum implementation in general do not meet the eligibility criteria for curriculum evaluation results of physical education and health subjects even with notes such as curriculum must keep up with the Times and in accordance with needs. In addition, the curriculum should be able to help the teacher to plan a lesson. The curriculum of the subjects of Physical Education Sports and health must be developed in detail referring to the objectives of National Education by giving priority to aspects that can be used and easy to use.